Teaching Large Classes: What Teachers Say and Do? - Chand, Gambhir Bahadur (Far Western Review, 2023)
Class size is often considered as one of the crucial factors that determines the effectiveness of teaching and learning in the classroom setting. In Nepal, large classes are very common in rural areas or even in urban areas. This study presents the findings of an empirical study on the challenges of teaching in large classes and how teachers are dealing with these challenges in Nepal. The main aim of this article is to explore the challenges of teaching in large classes and to find out the strategies they can be adapted to overcome these problems. The research was conducted by including 10 teachers teaching large classes, following a qualitative research design with a judgmental, non-random sampling procedure. Interviews and classroom observations were taken as the main research tools for the data collection. The research findings are divided into two categories: the challenges of teaching in large classes and how they deal with the large classes. Mainly, teachers found student participation, classroom management, disciplinary issues, and individual feedback as the main problems, and to deal with these problems, they explored various strategies like grouping students, changing seats of students, setting a code of conduct, and using alternative ways of giving feedback.